HOW TO TREAT VTEC IN CANCER PATIENTS IN THE ACUTE PERIOD? EXTENDED TREATMENT. THE ROLE OF DIRECT ORAL ANTICOAGULANTS. THE RESULTS OF HOKUSAI VTE CANCER STUDY - Yulia A. Fedotkina («REMEDIUM GROUP» Ltd., 2018)
Cancer is one of the most significant risk factors for venous thromboembolic complications (VTEC). The article discusses the features of the treatment of cancer patients with VTEC. The issues of alternative anticoagulant therapy are considered. The article presents the results of HOKUSAI VTE Cancer study, the first completed study to compare the efficacy and safety of a direct oral anticoagulant endoxaban with a low molecular weight heparin dalterapin for the treatment of VTEC in cancer patients.